(untitled) (Research, Society and Development, 2020)
The objective of the work was to determine the coefficients (a and b) of the Angström-Prescott equation and to determine the error in the estimate of global radiation for cities in the state of Tocantins. Meteorological data were obtained from the National Meteorological Institute (INMET) for the cities of Araguaína, Palmas, Pedro Afonso and Peixe, which were subjected to a filter and subsequently separated 70% for the generation of coefficients and 30% for validation (MBE, RMSE ed). The linear coefficients (a) ranged from 0.2291 to 0.3074 and angular (b) from 0.4295 to 0.4799 with a correlation between global radiation and insolation above 90%, where in the validation the error (MBE) ranged from 0.01 to 0.06 MJ m-2 d-1, spreading from 1.59 to 1.87 MJ m-2 d-1 and concordance index from 0.95 to 0.96. Individual Angström-Prescott coefficients can be used for each city evaluated with a correlation above 90%.